(untitled) (Research, Society and Development, 2025)
Oroantral Communication (OAC) is the opening between the maxillary sinus and the oral cavity. Oroantral Fistula (OAF) develops when the OAC does not close spontaneously, remains manifest, and is epithelialized. Removal of maxillary molars occasionally results in communication between the oral cavity and the maxillary sinus. If the maxillary sinus is extensively pneumatized, if there is little or no bone between the roots of the teeth and the maxillary sinus, and if the roots of the teeth are widely divergent, it is common for a bony portion of the sinus floor to be removed with the tooth or for a communication to be created even if the bone is not removed along with the tooth. If this problem occurs, appropriate measures are necessary to prevent a variety of sequelae. The two most worrisome sequelae are (1) postoperative sinusitis and (2) chronic oroantral fistula formation. The probability of these two problems occurring is related to the size of the oroantral communication and the conduct after exposure of the sinus. The present study aims to gather data from scientific articles in order to clarify the etiology, prevention and treatment of oroantral communication. For this literature review, national and international articles were searched in the Scielo, PubMed, Scopus, Lilacs and Google Scholar databases.